(untitled) (Meridiano 47 - Journal of Global Studies, 2017)
Resenha do livro: Moravcsik, Andrew; Milner, Helen V. (org.). Power, Interdependence and Nonstate Actors in World Politics. New Jersey: Princeton University Press, 2009. ISBN 978-0-691-14027-8